Correlation of Student Personal Skill with Learning Outcomes in Fundamental Chemistry Course - Syarifa Wahidah Al Idrus; Rahmawati (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to determine students' level of personal skills and to see the relationship between personal skills and learning outcomes of basic chemistry students in the first semester of the biology study program, FKIP UNRAM. The sample of this study is a saturated sample consisting of 49 students of the Biology Education Study Program, FKIP UNRAM. This research design is descriptive quantitative research with a quantitative correlational design. Data collection techniques are carried out by giving research instruments such as questionnaires. The results showed (1) semester 1 students of biology education FKIP Unram had personal skills mostly in the moderate category (58%), 2. there was a positive and significant relationship between personal skills and basic chemistry learning outcomes for Chemistry Education FKIP UNRAM students. The value of the coefficient of determination is 0.407. It shows that the social skill variable has a contribution to chemistry learning achievement by 40,7% while 59,3% is determined by other variables that are not examined